2011
DOI: 10.1177/1043986210396205
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Genetic Risk and Contact With the Criminal Justice System in a Sample of Hispanics

Abstract: A considerable amount of research has examined the genetic correlates to a wide array of antisocial behaviors. The results culled from this line of research have revealed that genes of the dopaminergic system are associated with criminal and delinquent involvement. Whether these associations would be detected with samples of various racial/ethnic origins remains to be determined. The current study addresses this gap in the literature by examining the association between genetic risk (as measured by dopaminergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…As mentioned above, previous findings regarding the association between genes and particular behavioural traits are highly contradictory3637. One possible reason for these disparities may be rooted in environmental factors38, and the present data together with our data on the Hadza42 illustrate a situation favouring this suggestion. Additionally, particular polymorphic loci may account for a relatively small proportion of phenotypic variance, and these effects may not be significant in relatively small samples of individuals with different socialisation experiences.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…As mentioned above, previous findings regarding the association between genes and particular behavioural traits are highly contradictory3637. One possible reason for these disparities may be rooted in environmental factors38, and the present data together with our data on the Hadza42 illustrate a situation favouring this suggestion. Additionally, particular polymorphic loci may account for a relatively small proportion of phenotypic variance, and these effects may not be significant in relatively small samples of individuals with different socialisation experiences.…”
Section: Discussionsupporting
confidence: 50%
“…One possible solution for this situation is to obtain a very large sample; another possibility is the generation of biologically founded multilocus genetic profiles reflecting the cumulative effects of multiple polymorphic loci of known functionality on a specific behaviour49. In accord with this approach, Beaver and Chavian created the Genetic Risk Index for criminal involvement in Hispanics based on three dopaminergic gene polymorphisms and demonstrated its effectiveness38. Other authors proposed the construction of a multilocus genetic profile score based on five functional polymorphic loci for dopamine signalling and reported that it accounted for 10.9% of the inter-individual variability in reward-related VS reactivity50.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was not the intent of prior research (Beaver, 2011). Fourth, and finally, prior researchers examining the role of genetic factors in CJ processing have examined the impact of measured genes (Beaver & Chaviano, 2011;. Researchers have become increasingly aware, however, that candidate gene research has some inherent limitations (Chabris, Lee, Cesarini, Benjamin, & Laibson, 2015;Dick et al, 2015).…”
Section: The Current Studymentioning
confidence: 99%